Epidemiological profile of gestational and congenital syphilis in the State of Piaui in the period 2017 to 2020 (Research, Society and Development, 2020)
Objective: To analyze the epidemiological profile of gestational and congenital syphilis in the state of Piauí in the period from 2017 to 2020. Method: This study is a systematic review, based on data in the virtual health library-bvs and PEDro database, using the descriptors: syphilis; gestation; Piauí; epidemiology. The search in the database took place between March and April 2020. Results: In the virtual health library (bvs) database, a total of 45 articles were found on the topic addressed and in the PEDro database, 15 were found. Of these articles, only 07 were selected because they met the inclusion and exclusion criteria. Conclusion: Thus, Piauí needs an improvement in its epidemiological surveillance in order to obtain a reduction in the incidence and mortality rates due to congenital syphilis. It is emphasized that such preventive practices and assistance must involve the entire multidisciplinary health team.